Overview of distinct 5-methylcytosine profiles of messenger RNA in normal and knock-down NSUN2 colorectal cancer cells - Lin, Yu; Zhao, Zhifang; Nie, Wenqiang; Huang, Manting; Cai, Jiazhong; Wang, Yadong; Wang, Hesong; Huang, Yongmei; Bai, Yang (Frontiers in Genetics, 2023)
Background: There is growing evidence that RNA methylation is closely related to the occurrence of cancer and its malignant biological behavior. However, as an important and widely distributed methylation modification, the distribution and role of 5-methylcytosine (m5C) in rectal cancer (CRC) is not fully understood. Methods: In this study, we used methylated RNA immunoprecipitation sequencing to identify m5C peaks on mRNA in HCT15 cells and sh-NSUN2 HCT15 cells, understand which transcripts are modified by m5C, and characterize the distribution of m5C modifications. In addition, we performed further bioinformatics analysis of the detected data to initially clarify the potential function of these m5C-modified transcripts. Results: We found significant differences in the distribution of m5C between HCT15 cells and sh-NSUN2 HCT15 cells, suggesting that m5C is likely to play a key role in the pathogenesis of CRC. In addition, GO enrichment analysis showed that genes altered by the m5C peak play a key role in phylogeny, synaptic membrane, and transcription factor binding. KEGG pathway analysis showed that these genes are enriched in some important pathways of cancer regulation, such as the ECM receptor interaction pathway, the circadian pathway, and the cAMP signaling pathway. Conclusions: Our results revealed different distribution patterns of m5C in in HCT15 cell and sh-NSUN2 HCT15 cell and provided new insights into a novel function of m5C RNA methylation of mRNA in CRC progression.